The Impact Of Competencies On Wages Of Employees In The Context Of Employers’ Expectations – Poland In The Light Of Eu Countries - Topolewska, Kamila; Topolewski, Łukasz (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: Competencies are an important feature from the perspective of both the employer and the job candidate. On the one hand, the employer is looking for candidates with specific competencies on the market and is willing to pay a specific salary for them. On the other hand, from the perspective of the job candidate, it is important to know which competencies are the best paid. In this way, the job candidate can direct their professional development in order to gain these competencies. Hence, research was undertaken to identify the best paid competencies. Aim: The purpose of this article is to identify the competencies of employees that determine obtaining a salary at least at the level of the average salary in the economy. Results: Based on individual data from Poles derived from the Human Capital Balance for 2021 (partially 2022), three logistic regression models were estimated: for the entire sample, for women, and for men. Significant variables for all models are age, education level, as well as willingness to work unusual hours required by the employer, willingness to travel frequently. It is worth considering which characteristics and competencies are specific to each model and positively influence the receipt of a high salary. Thus, in the case of the general model, gender, possession of a category B driver’s license and the ability to use a computer, tablet and smartphone turn out to be important. In the case of women, the ability to use specialized computer programs, as well as to work with people of different nationalities, influences higher salaries. For men, the competency that gives them the opportunity for higher salaries is analyzing information and drawing conclusions.